2021
DOI: 10.1101/2021.02.04.429873
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Little evidence the standard genetic code is optimized for resource conservation

Abstract: Shenhav & Zeevi (Science, 2020, 370:683-687) propose nitrogen and carbon conservation as optimization principles in the standard genetic code that are not confounded by the established optimizations for polar requirement and hydropathy. We show their results for nitrogen conservation are highly sensitive to their choice of null model and their results for carbon conservation are confounded by molecular volume.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Given how little we know about the actual process of the origin of the SGC, it is unclear which of the above two ways of generating RGCs is more meaningful and whether there are other more meaningful ways than these two ways. Rozhonova and Payne (2021) reported that, when the original ERMC was used, consistent evidence for the optimization of the SGC in nitrogen conservation was found in only one of the ten different ways of RGC generation tried.…”
Section: Methodsmentioning
confidence: 99%
“…Given how little we know about the actual process of the origin of the SGC, it is unclear which of the above two ways of generating RGCs is more meaningful and whether there are other more meaningful ways than these two ways. Rozhonova and Payne (2021) reported that, when the original ERMC was used, consistent evidence for the optimization of the SGC in nitrogen conservation was found in only one of the ten different ways of RGC generation tried.…”
Section: Methodsmentioning
confidence: 99%